A review on: anti-hyperglycaemic activity of potential herbal plants - Badri, Sireesha; V, Sushma Sree; CH, Hema; J, Rukmini; Desu, Prasanna Kumar (International Journal of Indigenous Herbs and Drugs, 2025)
Diabetes mellitus is a chronic, multifactorial metabolic disorder that has emerged as one of the most formidable public health challenges of the 21st century. Current therapeutic regimens, though effective in the short term, are often constrained by adverse effects, high cost, and diminished efficacy over prolonged use, highlighting the urgent need for complementary or alternative approaches. Traditional systems of medicine, including Ayurveda, Unani, and Traditional Chinese Medicine, have long emphasized the role of herbal plants in managing hyperglycemia. These natural agents are rich in diverse bioactive compounds-such as alkaloids, flavonoids, terpenoids, saponins, and glycosides that act synergistically through multiple mechanisms. They can stimulate insulin secretion, enhance pancreatic β-cell regeneration, improve peripheral glucose uptake, inhibit carbohydrate-digesting enzymes, modulate hepatic metabolism, and protect against oxidative stress-induced complications.